Problems Associated With Hemodialysis and Travel. Issue 4 (20th April 2014) - Corbett, Richard W.; Prout, Virginia; Haynes, Deborah; Edwards, Claire; Frankel, Andrew H.
Abstract : Background: While there is a recognized risk of hepatitis C acquisition associated with dialysis away from the "home" center, there is little documented data on the effect that dialysis while traveling has on the dialysis patient's health. This study was designed to examine the incidence of travel within a hemodialysis population and to ascertain whether travel was associated with morbidity for patients on hemodialysis. Methods: Travel data were collected prospectively over a 6‐month period, from April 2009, for all patients receiving maintenance hemodialysis across our dialysis centers. Biochemical, microbiological, and hematological parameters as well as hepatitis serology and antibiotic starts were recorded for 12 weeks prior to and following dialysis away from center. Results: A total of 172 individuals traveled on 200 occasions. The blood stream infection rate for travelers with a central venous catheter was 0.25 versus 0.83/1, 000 access days ( p  = 0.038) in the 12 weeks pre‐travel versus post‐travel. Parenteral and oral antibiotic starts were both significantly elevated post‐travel and were mainly instituted for either chest or urinary sepsis. There was evidence of raised inflammatory markers and anemia on return to center but no evidence of hepatitis B or hepatitis C seroconversion. Conclusions: Travel and dialysis away from a patient's usual hemodialysis unit is a common occurrence but is associated with an increased risk of bacterial infection, anemia, and inflammatory response. This study provides evidence for the concern that hemodialysis away from center is associated with increased morbidity.